2020
DOI: 10.21203/rs.3.rs-105121/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility of Delivering Parent-Implemented NDBI Interventions in Low Resource Regions: A Pilot Randomized Controlled Study

Abstract: Background: This implementation feasibility study was conducted to determine whether an evidence-based parent -implemented distance-learning intervention model for young children at high likelihood of having ASD could be implemented at fidelity by Part C community providers and by parents in low resource communities.Methods: The study used a community academic partnership model to adapt an evidence-based intervention tested in the current pilot trial involving randomization by agency in four states and enrollm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…To address some of these concerns, NDBI researchers have examined the effectiveness of various streamlined approaches for training community-based providers via online instruction (e.g., Rogers et al, 2020;Rooks-Ellis et al, 2020;Vismara et al, 2009), in vivo instruction (e.g., Stahmer et al, 2020), or a combination of the two (e.g., Chang et al, 2016;Shire et al, 2017). Results have been mixed with regard to post-training fidelity.…”
Section: Training Community-based Providersmentioning
confidence: 99%
“…To address some of these concerns, NDBI researchers have examined the effectiveness of various streamlined approaches for training community-based providers via online instruction (e.g., Rogers et al, 2020;Rooks-Ellis et al, 2020;Vismara et al, 2009), in vivo instruction (e.g., Stahmer et al, 2020), or a combination of the two (e.g., Chang et al, 2016;Shire et al, 2017). Results have been mixed with regard to post-training fidelity.…”
Section: Training Community-based Providersmentioning
confidence: 99%
“…With this in mind, there has been growing interest to embed early ASD interventions within the EI system (Stahmer et al 2017 ; Vivanti et al 2018 ). Recent research has suggested that, when NDBIs are moved into the EI system, they are perceived as feasible and acceptable by EI providers and may have positive outcomes for families of young children with ASD and social communication delays, even if delivered at somewhat low intensity (Stahmer et al 2017 ; Rogers et al 2020a ). This research has been foundational in building an understanding of how to translate NDBIs into systems naturally positioned to serve both children with a known diagnosis of ASD in addition to children with an increased likelihood of having ASD (Vivanti et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these studies found that coaching was effective in improving parent use of ESDM techniques and that child outcomes also improved in one or more domains (e.g., Vismara et al, 2009Vismara et al, , 2012Vismara et al, , 2013Waddington et al, 2021;Zhou et al, 2018). Other P-ESDM research found outcomes in favor of parent change but not child change (e.g., Rogers et al, 2019Rogers et al, , 2020Vismara et al, 2018). Finally, one P-ESDM study found no significant difference between coaching and control groups for either parent or child outcomes (Rogers et al, 2012a, b).…”
mentioning
confidence: 99%
“…Another limitation of the current body of ESDM research has to do with the inclusion/exclusion criteria applied to parents. Many studies excluded children whose primary caregiver met one of the following criteria: (a) self-reported substance abuse and/or significant mental illness (e.g., Rogers et al, 2012aRogers et al, , b, 2019; (b) lived farther than a specified distance from the University clinic that housed the study (e.g., Rogers et al, 2014Rogers et al, , 2019; and/or (c) did not meet various criteria for spoken and/or written English language ability (e.g., Rogers et al, 2020;Vismara et al, 2018). While none of these criteria is unreasonable in the context of a research efficacy study, they become untenable when applied to publicly-funded community services where families rightfully expect equitable access regardless of their child's diagnosis, their own language/literacy skills, and their ability to participate with regularity.…”
mentioning
confidence: 99%
See 1 more Smart Citation